Etica, empresa y desarrollo humano en la aldea global - Arévalo, Hugo; Huamán, Josefina; Quesada, Francisco Miró ([Lima]: INDEHU; CEDAL, 1999)
"Hugo Arévalo, Josefina Huamán, Francisco Miró Quesada,... et al. Onder toezicht van NCOS België"